Numerical Computation of Extrusion and Draw-extrusion Cable-coating Flows with Polymer Melts - Webster M. F.; Al-Muslimawi A.; Jahromi H. R. (Applied Rheology, 2014)
This paper is concerned with the numerical solution of polymer melt flows of both extrudate-swell and tube-tooling die-extrusion coatings, using a hybrid finite element/finite volume discretisation fe/fv. Extrudate-swell presents a single dynamic freesurface, whilst the complex polymer melt coating flow exhibit two separate free-surface draw-down sections to model, an inner and outer conduit surface of the melt. The interest lies in determining efficient windows for process control over variation in material properties, stressing levels generated and pressure drop. In this respect, major rheological influences are evaluated on the numerical predictions generated of the extensional viscosity and Trouton ratio, when comparing solution response for an exponential Phan-Thien Tanner (EPTT, network-based) model to that for a single extended Pom-Pom (SXPP, kinematic-based) model. The impact of shear-thinning is also considered. Attention is paid to the influence and variation in Weissenberg number We, solvent-fraction β (polymeric concentration), and second normal stress difference N2 (ξ parameter for both EPTT, and a anisotropy parameter for SXPP). The influence of model choice and parameters upon field response is described in situ through, pressure, shear and strain-rates and stress. The numerical scheme solves the momentum-continuity- surface equations by a semi-implicit time-stepping incremental Taylor-Galerkin/pressure-correction finite element method, whilst invoking a cell-vertex fluctuation distribution/median-dual-cell finite volume approximation for the first-order space-time hyperbolic-type stress evolution equation.